2011
DOI: 10.1099/mic.0.050005-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of IcmF of the type VI secretion system in an avian pathogenic Escherichia coli (APEC) strain

Abstract: The intracellular multiplication factor (IcmF) protein is a component of the recently described type VI secretion system (T6SS). IcmF has been shown to be required for intra-macrophage replication and inhibition of phagosome-lysosome fusion in Legionella pneumophila. In Vibrio cholerae it is involved in motility, adherence and conjugation. Given that we previously reported that two T6SS genes (hcp and clpV) contribute to the pathogenesis of a septicaemic strain (SEPT362) of avian pathogenic Escherichia coli (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
64
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 49 publications
6
64
1
2
Order By: Relevance
“…It has been reported that the ⌬icmF strain decreased the expression of flhC, flhD, flgM, and fliA flagellar genes at the level of transcription in avian-pathogenic E. coli (APEC) (15). Our results suggested that deletion of T6SS or its key genes was detrimental to the expression of the flagellar regulon at the level of transcription, as was found in E. coli (15).…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…It has been reported that the ⌬icmF strain decreased the expression of flhC, flhD, flgM, and fliA flagellar genes at the level of transcription in avian-pathogenic E. coli (APEC) (15). Our results suggested that deletion of T6SS or its key genes was detrimental to the expression of the flagellar regulon at the level of transcription, as was found in E. coli (15).…”
Section: Discussionsupporting
confidence: 50%
“…It has been reported that the T6SS contributes to the virulence development of various pathogens and is often activated upon contact with target cells for the secretion of effector proteins (1)(2)(3)(4)(5)(6)(7)(14)(15)(16)(17). The expression and assembly of the T6SS are tightly controlled at both the transcriptional and posttranscriptional levels (12,13,18).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The cytosolic domain has a conserved Walker-A motif, indicating a function as an ATPase during secretion, consistent with the finding that IcmF mutations prevent Hcp secretion (Pukatzki et al, 2006;Zheng & Leung 2007). An icmF mutant of avian pathogenic E. coli had decreased adherence to and invasion of epithelial cells, as well as decreased intra-macrophage survival and was also defective for biofilm formation on abiotic surfaces (Pace et al, 2011).…”
Section: Introductionmentioning
confidence: 99%